The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1159/000445037
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma D-Dimer Indicates Unfavorable Outcome of Acute Ischemic Stroke Patients Receiving Intravenous Thrombolysis

Abstract: Background: D-dimer is a fibrin degradation product and a possible marker of thromboembolic events. The aim of this study was to investigate the relationship between D-dimer levels and outcome in acute ischemic stroke (AIS) patients receiving intravenous thrombolysis. Methods: This retrospective study included AIS patients who received intravenous thrombolysis with recombinant tissue plasminogen activator (rt-PA) and provided plasma D-dimer level within 24 h after stroke onset during 2009 and 2014 at a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 25 publications
1
54
0
2
Order By: Relevance
“…Especially D-dimer was effective in identifying IS etiology [181,182] and showed good prognostic accuracy as predictor of short- and long-term worse outcome [182,183,185,186]. Similar results were also reported for E-selectin and VCAM-1, but those data required further validation in additional large-cohort studies [184].…”
Section: Inflammatory Mediators As Potential Diagnostic or Prognosmentioning
confidence: 76%
See 1 more Smart Citation
“…Especially D-dimer was effective in identifying IS etiology [181,182] and showed good prognostic accuracy as predictor of short- and long-term worse outcome [182,183,185,186]. Similar results were also reported for E-selectin and VCAM-1, but those data required further validation in additional large-cohort studies [184].…”
Section: Inflammatory Mediators As Potential Diagnostic or Prognosmentioning
confidence: 76%
“…Furthermore, specific challenges regarding biomarkers of central nervous tissue include the penetration of BBB and the lack of correlation between functional symptoms and volume (as opposed to location) of injured tissue. According to pathophysiological processes underlying IS, potential inflammatory biomarkers may be classified as released by: (i) astroglial activation and neuronal injury (Table 1) [146,147,148,149,150,151,152,153,154,155,156,157]; (ii) systemic inflammatory response (Table 2) [158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177,178,179]; (iii) dysfunctional endothelium (Table 3) [180,181,182,183,184,185,186] (Figure 4). …”
Section: Inflammatory Mediators As Potential Diagnostic or Prognosmentioning
confidence: 99%
“…D-dimer, is a well characterized sensitive marker of thrombosis with fiber dissolving activity (49), which had a predictive value for AT in patients with NSAID-induced GIB in the present study. D-dimer is a degradation product produced during the hydrolysis of fibrinolytic enzymes and is a specific indicator of hypercoagulability and secondary fibrinolysis (49). Secondary fibrinolytic activity was primarily enhanced in patients with AT, who typically present with reduced levels of plasminogen and increased levels of D-dimer (50).…”
Section: Discussionmentioning
confidence: 51%
“…A study by Ridker et al (54) found that the presence of D-dimers was closely associated with ischemic cardiomyopathy. The elevated levels of D-dimers indicate an increased risk of MI, however, D-dimer was not an independent predictor (49). Previous studies have suggested that the activation of blood coagulation was an independent risk factor of cerebral infarction, where the D-dimer level and the degree of cerebral infarction were linearly correlated, and could be used to infer the prognosis of patients with cerebral infarction (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…The available investigations of stroke have shown a correlation between D-dimer levels and functional outcomes and the prognostic value of D-Dimer in several different types of population with AIS [35][36][37][38][39]. Nam et al [35] and Nezu et al [36] found a predictive role of D-dimer only in patients with cryptogenic stroke.…”
Section: Discussionmentioning
confidence: 99%